Physical boundaries and city boundaries: consequences for crime patterns on street segments? - Kim, Young-An (Crime & delinquency, 2018)
Scholars have theorized how spatial boundaries (edges) can be important for understanding the location of crime, yet the empirical relationship between spatial boundaries in the environment and levels of crime is relatively less explored compared with other features of the environment. The current study extends the literature by not only studying three types of physical boundaries—interstate highways, parks, and rivers—but also one nonphysical and relatively less visible boundary—city boundaries. We analyze the relationship between crime in street segments and nearness to these four types of edges in the Southern California area. We measure nearness to these boundaries in two manners: (a) whether or not the segment is adjacent to the feature and (b) how far in physical distance the segment is to the feature.